A CASE OF AUTOSOMAL DOMINANT OSTEOPETROSIS TYPE 2 WITH A CLCN7 GENE MUTATION - Noordin, Mazidah; Maju, Abdul Salam Amir Hamzah; Nor, Noor Shafina Mohd (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Non-classical congenital adrenal hyperplasia (NCCAH) usually has a late presentation as compared to classical CAH as the presentation is often atypical. Presentation in boys can be asymptomatic through family screening or with clinical presentation such as signs of premature adrenarche and growth spurt. CASE MFI, a 4 year-4-month-old male was referred to the paediatric endocrine clinic with complaints of body odour for 2 months, associated with pubic hair and acne. He seemed to be taller compared to his peers with a recent height spurt. His parents are not consanguineous with no significant family history. He has facial acne with signs of precocious puberty. He has Tanner II genitalia with stretched penile length of 7 cm, presence of pubic hair, and bilateral testicular volume of 4 ml. Baseline investigations revealed low cortisol level, elevated 17-hydroxyprogesterone (17OHP) and detectable testosterone levels. Short synacthen test showed low cortisol level, with significantly elevated 17-OHP with a peak of 931 nmol/L. Both sodium and potassium were normal, however, renin was elevated at 166.5 mU/L (normal range 4.2 – 59.7) with aldosterone at a lower range of normal at 155 pmol/L (normal range 102 – 859). LHRH test showed pubertal respond with peak LH at 11.4 IU/L. Bone age was 7 years more advanced than his age, at 11.4 years. Genetic test for CAH panel was not performed due to financial constraint. Diagnosis of NCCAH with central precocious puberty was made and hydrocortisone, fludrocortisone and GnRH analogue were started. CONCLUSION This case illustrates an unusual presentation of a male patient with NCCAH complicated by central precocious puberty due to androgen excess that has activated the central pubertal response. Treatment aims to control the CAH as well as suppress puberty with GnRH analogue, with the hope of preserving the patient’s final adult height.